2015
DOI: 10.1074/jbc.m114.615211
|View full text |Cite
|
Sign up to set email alerts
|

A Pore-Forming Toxin Requires a Specific Residue for Its Activity in Membranes with Particular Physicochemical Properties

Abstract: Background: It is unclear how actinoporins adapt to the broad range of physicochemical landscapes of biological membranes. Results: A single mutation in fragaceatoxin C (an actinoporin) prevents the formation of lytic pores in membranes in the liquid-ordered phase. Conclusion: Phe-16 is critical for pore formation of fragaceatoxin C in cholesterol-rich membranes. Significance: Site-directed mutagenesis generates lipid phase-sensitive pore-forming proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 71 publications
(82 reference statements)
4
25
0
Order By: Relevance
“…This bore strong similarities to CRAC motifs that have been widely observed and characterized in many eukaryotic transmembrane proteins (42)(43)(44)(45)(46). A similar role of specific lipids in membrane partitioning of the N-terminal transmembrane helix for actinoporins, equinatoxin II, and fragaceatoxin C (FraC) has been demonstrated (47,48), suggesting conservation of membrane insertion mechanisms among the α-PFT family of proteins. In addition to stabilizing the N-terminal inserted state, MD simulations revealed that cholesterol played an important role in the ensuing stages of oligomerization by preferentially binding to a previously uncharacterized pocket formed between two adjacent β-tongues.…”
Section: Discussionsupporting
confidence: 64%
“…This bore strong similarities to CRAC motifs that have been widely observed and characterized in many eukaryotic transmembrane proteins (42)(43)(44)(45)(46). A similar role of specific lipids in membrane partitioning of the N-terminal transmembrane helix for actinoporins, equinatoxin II, and fragaceatoxin C (FraC) has been demonstrated (47,48), suggesting conservation of membrane insertion mechanisms among the α-PFT family of proteins. In addition to stabilizing the N-terminal inserted state, MD simulations revealed that cholesterol played an important role in the ensuing stages of oligomerization by preferentially binding to a previously uncharacterized pocket formed between two adjacent β-tongues.…”
Section: Discussionsupporting
confidence: 64%
“…4A) is enthalpy-driven (DH°W T = À9.9 ± 0.5 kcal mol À1 ) and shows moderate affinity for lipids (K D WT = 16 ± 9 lM; DG°= À6.5 ± 0.3 kcal mol À1 ). The enthalpic component is partially compensated by the entropic component (ÀTDS°= 3.3 ± 0.8 kcal mol À1 ), as previously described for sticholysin II and FraC in other lipid mixtures [18,22]. In contrast, binding of V60E to liposomes generated a weak exothermic signal, nor sufficient for a reliable quantification of the thermodynamic parameters (Fig.…”
Section: Calorimetric Studiesmentioning
confidence: 53%
“…The biggest cavity in each structure depicted in purple was found in CDR1 segment and calculated with CASTp server [31]. dependent on the cell membrane environment [45]. (A) 6aJL2, (B) 6a-R25G, and (C) AR.…”
Section: Discussionmentioning
confidence: 99%
“…Check marks indicate that the respective interaction is present in the corresponding protein while dashes indicate the missing interaction. dependent on the cell membrane environment [45]. The manner in which k6 variable domain oligomers could be interacting with a specific cellular membrane might be influenced by its corresponding mutations resulting in different cellular internalization processes and phenotypic transformations [46][47][48].…”
Section: Discussionmentioning
confidence: 99%